Manufacturing method of superabsorbent resin

By adding a reducing agent to hydrogel polymers to induce additional polymerization and crosslinking, the method addresses the issue of residual monomers and water-soluble components in superabsorbent resins, improving their performance and preventing rewetting in sanitary products.

JP7601426B2Active Publication Date: 2024-12-17LG CHEM LTD
View PDF 19 Cites 0 Cited by

Patent Information

Application Number
JP2022565675
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-01-12
Filing Date
2022-01-14
Publication Date
2024-12-17
Estimated Expiration
2042-01-14

AI Technical Summary

Technical Problem

Existing superabsorbent resins face challenges in minimizing the content of residual monomers and water-soluble components, leading to issues like rewetting and leakage, particularly when subjected to external pressure, which affects their hygiene and performance in sanitary products.

Method used

A method involving the addition of a reducing agent containing sulfur-containing anions during the cutting of hydrogel polymers to induce an oxidation/reduction reaction with a thermal polymerization initiator, facilitating additional polymerization of residual monomers and reducing water-soluble components, followed by crosslinking processes to form a surface crosslinked layer.

Benefits of technology

The method effectively reduces residual monomers and water-soluble components, enhancing the superabsorbent resin's ability to maintain water absorption performance and prevent rewetting, making it suitable for sanitary materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601426000001
    Figure 0007601426000001
  • Figure 0007601426000002
    Figure 0007601426000002
Patent Text Reader

Abstract

The present invention relates to a method for producing a superabsorbent polymer, and more specifically, to a method for producing a superabsorbent polymer in which the contents of residual monomers and water-soluble components are simultaneously reduced by adding a reducing agent capable of undergoing an oxidation / reduction reaction with a thermal polymerization initiator before drying a hydrogel polymer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of priority based on Korean Patent Application No. 10-2021-0005519 filed on January 14, 2021, and Korean Patent Application No. 10-2022-0004887 filed on January 12, 2022, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference.

[0002] The present invention relates to a method for producing a superabsorbent polymer, more specifically, to a method for producing a superabsorbent polymer having a reduced content of water-soluble components while minimizing the content of residual monomers by adding a reducing agent capable of undergoing an oxidation / reduction reaction with a thermal polymerization initiator before chopping a hydrogel polymer. [Background technology]

[0003] Super absorbent polymer (SAP) is a synthetic polymeric substance that has the ability to absorb 500 to 1,000 times its own weight in water, and is given different names by different developers, such as SAM (Super Absorbency Material) and AGM (Absorbent Gel Material). These super absorbent polymers first came into practical use as sanitary products, and are now widely used as soil water retention agents for horticulture, water stoppers for civil engineering and construction, seedling sheets, freshness preserving agents in the food distribution field, and materials for packs.

[0004] Such superabsorbent polymers are widely used in the field of sanitary materials, such as diapers and sanitary napkins. In the sanitary materials, the superabsorbent polymers are generally contained in a dispersed state in the pulp. However, in recent years, efforts have been made to provide sanitary materials, such as diapers, with thinner thicknesses, and as part of these efforts, the pulp content has been reduced or even no pulp is used at all, so-called pulpless diapers, have been actively developed.

[0005] Furthermore, to be widely used in sanitary materials, they must have high absorbency against moisture and must not lose absorbed moisture even when subjected to external pressure. In addition, they must maintain their shape well even when absorbing water and expanding in volume (swelling), demonstrating excellent permeability.

[0006] In addition, pressure is applied to sanitary products such as diapers and sanitary napkins due to the weight of the user. In particular, if pressure due to the weight of the user is applied to the superabsorbent polymer used in sanitary products such as diapers and sanitary napkins after the polymer absorbs liquid, a rewet phenomenon in which some of the liquid absorbed by the superabsorbent polymer seeps out again, and a leakage phenomenon in which urine leaks out may occur.

[0007] In particular, when the superabsorbent polymer contains water-soluble components having short chains that have been polymerized but have not been crosslinked, this further leads to the rewetting phenomenon, and when the superabsorbent polymer contains a high content of residual monomers that have not been polymerized, this causes hygiene problems.

[0008] Therefore, various attempts have been made to simultaneously reduce the contents of water-soluble components and residual monomers in the superabsorbent polymer, but no concrete measures have been presented yet. Summary of the Invention [Problem to be solved by the invention]

[0009] Therefore, the present invention relates to a method for producing a superabsorbent polymer, which can minimize the content of residual monomers remaining in the superabsorbent polymer by adding a reducing agent containing a sulfur-containing anion during the shredding step of a hydrogel polymer, thereby causing an additional polymerization reaction during shredding, and can reduce the content of water-soluble components generated during drying. [Means for solving the problem]

[0010] In order to solve the above problems, the present invention provides A step of preparing a monomer composition including an acrylic acid monomer having an acidic group, at least a portion of which has been neutralized, an internal crosslinking agent, and a thermal polymerization initiator (step 1); a step of cross-linking the monomer composition to form a hydrogel polymer (step 2); mixing the hydrogel polymer with a reducing agent and then chopping the mixture (step 3); Step 4: drying and grinding the hydrogel polymer chopped in step 2 to produce a base resin; and and (5) further cross-linking the surface of the base resin in the presence of a surface cross-linking agent to form a surface cross-linked layer on at least a portion of the surface of the base resin. The reducing agent is at least one selected from the group consisting of sulfoxylates, sulfites, hydrogensulfites, and metabisulfites, and is used in an amount of at least 10 parts by weight based on 100 parts by weight of the thermal polymerization initiator. A method for producing a superabsorbent resin is provided. Effect of the Invention

[0011] According to the method for producing a superabsorbent polymer of the present invention, when a reducing agent having a specific structure containing a sulfur-containing anion is added during the shredding stage of a hydrogel polymer to produce a superabsorbent polymer, the remaining monomers are polymerized by an additional radical-initiated reaction caused by an oxidation / reduction reaction between the reducing agent and a thermal polymerization initiator during shredding, thereby reducing the content of the remaining monomers in the superabsorbent polymer. In addition, the additional polymerization reaction during shredding can reduce water-soluble components that may be produced when the shredded hydrogel polymer is dried. This makes it possible to produce a superabsorbent polymer in which the content of the residual monomers and the water-soluble components are simultaneously reduced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The terms used in this specification are merely used to describe exemplary embodiments and are not intended to limit the present invention. A singular expression includes a plural expression unless the context clearly indicates otherwise. In this specification, the terms "include", "comprise", "have" or "have" are intended to specify the presence of an implemented feature, step, component, or combination thereof, and should be understood not to preclude the possibility of the presence or addition of one or more other features, steps, components, or combinations thereof.

[0013] Although the present invention can be implemented in various forms through various modifications, specific embodiments are described in detail below, but it is to be understood that this is not intended to limit the present invention to the specific disclosed embodiments, and that the present invention includes all modifications, equivalents, and alternatives falling within the spirit and technical scope of the present invention.

[0014] Furthermore, the terminology used herein is for the purpose of referring to particular embodiments only and is not intended to limit the present invention, and the singular forms used herein include the plural forms unless the language clearly indicates otherwise.

[0015] The term "polymer" or "polymeric polymer" used in the present specification means a state in which an acrylic acid monomer, which is a water-soluble ethylenically unsaturated monomer, is polymerized, and can include all water content ranges or particle size ranges. Among the polymers, a polymer having a water content (water content) of about 40% by weight or more in a state after polymerization and before drying can be called a hydrogel polymer, and particles of such a hydrogel polymer that have been crushed and dried can be called a crosslinked polymer.

[0016] In addition, the term "superabsorbent resin particles" refers to a particulate material including a crosslinked polymer obtained by polymerizing an acrylic acid monomer containing acidic groups and at least a portion of the acidic groups being neutralized, and crosslinking the polymer with an internal crosslinking agent.

[0017] Furthermore, the term "super absorbent polymer" refers to a crosslinked polymer obtained by polymerizing an acrylic acid monomer containing acidic groups and at least a portion of which has been neutralized, or a powder-like base resin made of super absorbent polymer particles obtained by pulverizing the crosslinked polymer, depending on the context, or is used to encompass all of the crosslinked polymers or base resins that have been subjected to additional processes, such as surface crosslinking, regranulation into fine powder, drying, pulverization, classification, etc., to be in a state suitable for commercialization. Thus, the term "super absorbent polymer" is interpreted to include a plurality of super absorbent polymer particles.

[0018] For superabsorbent polymers to be widely used as sanitary materials, they must have excellent water absorption performance, and the residual monomers (RM) that remain in the superabsorbent polymer and cannot participate in polymerization, and the extractable contents (E / C) that participate in polymerization but have short chains that cannot be bonded to the main chain, must be reduced. However, it is not easy to simultaneously reduce the residual monomer content and the water-soluble content. The reason is that when a large amount of polymerization initiator is added to reduce the residual monomer content in the production of base resin, the water-soluble content increases, and when the polymerization initiator content is reduced to reduce the water-soluble content, the residual monomer content increases.

[0019] Therefore, the present inventors have confirmed that when a reducing agent capable of oxidizing / reducing with a thermal polymerization initiator is added before the drying process after the preparation of a hydrogel polymer, the content of residual monomers and water-soluble components can be simultaneously reduced without decreasing the water absorption rate and water absorption performance of the superabsorbent resin due to an additional radical initiation reaction caused by the reaction with the thermal polymerization initiator remaining without reacting in the polymerization process, and have completed the present invention. This is believed to be because the thermal polymerization initiator is reduced by the oxidation-reduction reaction between the remaining thermal polymerization initiator and the reducing agent, inducing an additional radical initiation reaction, which polymerizes the remaining monomers that could not participate in the polymerization, and also allows components that cannot be bonded to the main chain constituting the crosslinked polymer to be bonded to the main chain. In addition, the remaining thermal polymerization initiator has a side effect of destroying the main chain during high-temperature drying, but the side effect caused by high-temperature drying can be prevented by exhausting the remaining thermal polymerization initiator at a low temperature.

[0020] The superabsorbent polymer thus produced has an Ideal Hydrogel Index (IHI), calculated by the following Equation 1, which indicates the balance between water absorption performance, residual monomer content, and water-soluble component content, of 20 or more. As a result, the superabsorbent polymer has the properties of suppressing rewetting while maintaining water absorption performance, and reducing water-soluble components that are unsuitable for hygiene, and is therefore suitable for use in sanitary materials.

[0021] [Formula 1] Ideal Hydrogel Index(IHI)=(CRC+8.7) / [ln{E / C+(RM / 500)}]

[0022] In the above formula 1, CRC is the centrifugal retention capacity measured by the EDANA method NWSP241.0.R2; E / C is the content of water-soluble components contained in the superabsorbent polymer as measured by the EDANA method WSP270.2, RM means the content of residual monomer remaining in the superabsorbent polymer as measured by the EDANA method NWSP210.0.R2.

[0023] Hereinafter, each step of the method for producing a superabsorbent polymer will be described in more detail according to a specific embodiment of the present invention.

[0024] (Stage 1) In one embodiment of the method, step 1 is a step of preparing a monomer composition including an acrylic acid monomer having an acidic group, at least a portion of which is neutralized, an internal crosslinking agent, and a thermal polymerization initiator.

[0025] The acrylic acid monomer is a compound represented by the following formula 1:

[0026] [Chemical formula 1] R 1 -COOM 1

[0027] In the above Chemical Formula 1, R 1 is an alkyl group having 2 to 5 carbon atoms and containing an unsaturated bond, M 1 is a hydrogen atom, a monovalent or divalent metal, an ammonium group, or an organic amine salt.

[0028] Preferably, the acrylic acid monomer includes at least one selected from the group consisting of acrylic acid, methacrylic acid, and their monovalent metal salts, divalent metal salts, ammonium salts, and organic amine salts.

[0029] Here, the acrylic acid monomer may have an acidic group, and at least a part of the acidic group may be neutralized. Preferably, the monomer may be partially neutralized with an alkaline substance such as sodium hydroxide, potassium hydroxide, or ammonium hydroxide. In this case, the neutralization degree of the acrylic acid monomer may be 40 to 95 mol%, 40 to 80 mol%, or 45 to 75 mol%. The range of the neutralization degree can be adjusted according to the final physical properties. However, if the neutralization degree is too high, the neutralized monomer may precipitate and the polymerization may not proceed smoothly, and conversely, if the neutralization degree is too low, the water absorption of the polymer may be greatly reduced and the polymer may exhibit properties similar to elastic rubber, which is difficult to handle.

[0030] The concentration of the acrylic acid monomer is about 20 to about 60% by weight, preferably about 40 to about 50% by weight, based on the monomer composition including the raw material of the superabsorbent polymer and the solvent, and may be an appropriate concentration taking into consideration the polymerization time and reaction conditions, etc. However, if the concentration of the monomer is too low, the yield of the superabsorbent polymer may be low, causing problems in terms of economy, and conversely, if the concentration is too high, problems may occur in the process, such as partial precipitation of the monomer or reduced pulverization efficiency during pulverization of the polymerized hydrogel polymer, and the physical properties of the superabsorbent polymer may be reduced.

[0031] In addition, the term "internal crosslinking agent" used in this specification is a term used to distinguish it from a surface crosslinking agent for crosslinking the surface of superabsorbent resin particles described later, and plays a role in crosslinking and polymerizing the unsaturated bonds of the water-soluble ethylenically unsaturated monomer described above. The crosslinking in this step is carried out regardless of the surface or the inside, but when the surface crosslinking process of the superabsorbent resin particles described later is performed, the particle surface of the finally produced superabsorbent resin has a structure crosslinked by the surface crosslinking agent, and the inside has a structure crosslinked by the internal crosslinking agent.

[0032] As the internal crosslinking agent, any compound can be used as long as it can introduce crosslinking during polymerization of the acrylic acid-based unsaturated monomer.Specifically, as the internal crosslinking agent, a crosslinking agent having one or more functional groups that can react with the water-soluble substituent of the acrylic acid-based unsaturated monomer and one or more ethylenic unsaturated groups; or a crosslinking agent having two or more functional groups that can react with the water-soluble substituent of the monomer and / or the water-soluble substituent formed by the hydrolysis of the monomer can be used.

[0033] Non-limiting examples of the internal crosslinking agent include N,N'-methylenebisacrylamide, trimethylpropane tri(meth)acrylate, ethylene glycol di(meth)acrylate, polyethylene glycol (meth)acrylate, polyethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, polypropylene glycol (meth)acrylate, butanediol di(meth)acrylate, butylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, hexanediol di(meth)acrylate, triethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, dipentaerythritol pentaacrylate, glycerin tri(meth)acrylate, pentaerythritol tetraacrylate, allyl (meth)acrylate, ethylene glycol di(meth)acrylate, propylene ... Acrylate-based compounds such as acrylate; epoxy-based compounds such as ethylene glycol diglycidyl ether, diethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, tripropylene glycol diglycidyl ether, polypropylene glycol diglycidyl ether, neopentyl glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polytetramethylene glycol diglycidyl ether, glycerol diglycidyl ether, glycerol triglycidyl ether, diglycerol polyglycidyl ether, and polyglycerol polyglycidyl ether; triarylamine; propylene glycol; glycerin; or polyfunctional crosslinkers such as ethylene carbonate may be used alone or in combination of two or more, but are not limited thereto.

[0034] In the monomer composition, the internal crosslinking agent can be used in an amount of 0.01 to 5 parts by weight based on 100 parts by weight of the acrylic acid monomer. For example, the internal crosslinking agent can be used in an amount of 0.01 parts by weight or more, 0.05 parts by weight or more, 0.1 parts by weight or more, or 0.15 parts by weight or more and 5 parts by weight or less, 3 parts by weight or less, 2 parts by weight or less, 1 part by weight or less, or 0.7 parts by weight or less based on 100 parts by weight of the water-soluble ethylenically unsaturated monomer. If the content of the internal crosslinking agent is too low, crosslinking does not occur sufficiently, making it difficult to achieve strength above an appropriate level, and if the content of the internal crosslinking agent is too high, the internal crosslinking density increases, making it difficult to achieve the desired water retention ability.

[0035] In addition, the monomer composition further contains a polymerization initiator for initiating a polymerization reaction of the monomer. Such a polymerization initiator is not particularly limited as long as it is one that is generally used in the production of a highly water-absorbent resin.

[0036] Specifically, the polymerization initiator is used for thermal polymerization or photopolymerization. However, even in the photopolymerization method, a certain amount of heat is generated by irradiation with ultraviolet light or the like, and a certain amount of heat is generated by the progress of the polymerization reaction, which is an exothermic reaction, so that both a photopolymerization initiator and a thermal polymerization initiator can be used.

[0037] In one embodiment, the thermal polymerization initiator may be one or more selected from the group consisting of persulfate compounds, azo compounds, hydrogen peroxide, and ascorbic acid. Specifically, examples of persulfate compounds include sodium persulfate (Na2S2O8), potassium persulfate (K2S2O8), and ammonium persulfate ((NH4)2S2O8). Examples of azo compounds include 2,2-azobis(2-amidinopropane) dihydrochloride, 2,2-azobis-(N,N-dimethylene)isobutyramidine dihydrochloride, and the like. dihydrochloride, 2-(carbamoylazo)isobutylonitril, 2,2-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, 4,4-azobis-(4-cyanovaleric acid), etc. More diverse thermal polymerization initiators are clearly described in "Principle of Polymerization" by Odian (Wiley, 1981) p.203, and are not limited to the above examples.

[0038] More specifically, the thermal polymerization initiator may include a persulfate compound, for example, sodium persulfate (SPS; Na2S2O8) may be used as the thermal polymerization initiator.

[0039] The thermal polymerization initiator can be used in an amount of 0.05 to 0.25 parts by weight based on 100 parts by weight of the acrylic acid monomer. If the amount of the thermal polymerization initiator is less than 0.05, the polymerization rate is slowed down, and the amount of residual monomer is difficult to decrease because the additional radical initiation reaction by the reaction with the reducing agent cannot be sufficiently initiated. If the amount of the thermal polymerization initiator is more than 0.25 parts by weight, the amount of water-soluble components increases, which may cause rewetting of the superabsorbent resin.

[0040] The monomer composition may further include a photopolymerization initiator. The photopolymerization initiator may be any compound capable of forming radicals by the action of light such as ultraviolet light, and may be used without any limitation on its constitution.

[0041] The photopolymerization initiator may be one or more selected from the group consisting of benzoin ether, dialkyl acetophenone, hydroxyl alkyl ketone, phenyl glyoxylate, benzyl dimethyl ketal, acyl phosphine, and α-aminoketone. Meanwhile, as a specific example of acylphosphine, commercially available lucirin TPO, i.e., diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide, may be used. More various photoinitiators are well described in "UV Coatings: Basics, Recent Developments and New Application" (Elsevier, 2007), p. 115, by Reinhold Schwalm, and are not limited to the above examples.

[0042] The photopolymerization initiator can be used in an amount of 0.001 to 0.010 parts by weight based on 100 parts by weight of the acrylic acid monomer. If the concentration of the photopolymerization initiator is too low, the polymerization rate is slow, and if the concentration of the photopolymerization initiator is too high, the molecular weight of the superabsorbent resin is small, which may result in non-uniform physical properties.

[0043] The monomer composition may further contain additives such as a thickener, a plasticizer, a storage stabilizer, and an antioxidant, if necessary.

[0044] The monomer composition containing the monomer may be in a solution state dissolved in a solvent such as water, and the solid content in the monomer composition in such a solution state, that is, the concentration of the monomer, the internal crosslinking agent, and the polymerization initiator, can be appropriately adjusted in consideration of the polymerization time, reaction conditions, etc. For example, the solid content in the monomer composition may be 10 to 80% by weight, or 15 to 60% by weight, or 30 to 50% by weight.

[0045] When the monomer composition has a solid content in this range, it is possible to eliminate the need to remove unreacted monomers after polymerization by utilizing the gel effect phenomenon that occurs in the polymerization reaction of a high-concentration aqueous solution, and it may be advantageous to adjust the pulverization efficiency when pulverizing the polymer described below.

[0046] In this case, the solvent that can be used is not limited in composition as long as it can dissolve the above-mentioned components, and for example, one or more selected from water, ethanol, ethylene glycol, diethylene glycol, triethylene glycol, 1,4-butanediol, propylene glycol, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol monomethyl ether acetate, methyl ethyl ketone, acetone, methyl amyl ketone, cyclohexanone, cyclopentanone, diethylene glycol monomethyl ether, diethylene glycol ethyl ether, toluene, xylene, butyrolactone, carbitol, methyl cellosolve acetate, and N,N-dimethylacetamide can be used in combination.

[0047] (Stage 2) Next, the monomer composition is cross-linked to prepare a hydrogel polymer. The polymerization of the monomer composition is not particularly limited as long as it is a commonly used polymerization method.

[0048] Specifically, polymerization methods are broadly divided into thermal polymerization and photopolymerization depending on the polymerization energy source. Thermal polymerization is usually carried out in a reactor having a stirring shaft such as a kneader, and photopolymerization is usually carried out in a reactor equipped with a movable conveyor belt. However, the above-mentioned polymerization methods are merely examples, and the present invention is not limited to the above-mentioned polymerization methods.

[0049] For example, the hydrogel polymer obtained by thermal polymerization by supplying hot air to a reactor such as a kneader equipped with an agitator shaft as described above or by heating the reactor may be in the form of a hydrogel polymer discharged from the outlet of the reactor, which may be in the form of several centimeters to several millimeters, depending on the form of the agitator shaft equipped in the reactor. Specifically, the size of the obtained hydrogel polymer varies depending on the concentration of the monomer composition injected and the injection speed, but a hydrogel polymer having a weight average particle size of 2 to 50 mm is usually obtained.

[0050] In addition, when photopolymerization is carried out in a reactor equipped with a movable conveyor belt as described above, the form of the hydrogel polymer obtained may be a sheet-like hydrogel polymer having the width of the belt. At this time, the thickness of the polymer sheet varies depending on the concentration and injection speed of the monomer composition injected, but it is preferable to supply the monomer composition so that a sheet-like polymer having a thickness of about 0.5 to about 5 cm is obtained. When the monomer composition is supplied so that the thickness of the sheet-like polymer is excessively thin, the production efficiency is low, which is undesirable, and when the thickness of the sheet-like polymer exceeds 5 cm, the polymerization reaction may not occur evenly over the entire thickness due to the excessively thick thickness.

[0051] Meanwhile, in order to increase the water absorption rate of the superabsorbent resin, a foaming agent capable of introducing a pore structure into the superabsorbent resin during cross-linking polymerization of the monomer composition may be additionally used. As such a foaming agent, any compound known in the art that generates bubbles during the polymerization step may be used without limitation, and for example, a carbonate-based foaming agent or an encapsulated foaming agent may be used.

[0052] As the carbonate-based foaming agent, for example, one or more selected from the group consisting of sodium bicarbonate, sodium carbonate, potassium bicarbonate, potassium carbonate, calcium bicarbonate, calcium carbonate, magnesium bicarbonate, and magnesium carbonate can be used.

[0053] Specifically, the carbonate-based foaming agent can be used in an amount of 0.005 to 1 part by weight based on 100 parts by weight of the acrylic acid-based monomer. If the content of the foaming agent is less than 0.005 part by weight, the foaming agent plays a small role, and if the content of the foaming agent exceeds 1 part by weight, the crosslinked polymer has too many pores, resulting in a decrease in gel strength and density of the produced superabsorbent resin, which may cause problems in distribution and storage.

[0054] In addition, the encapsulated foaming agent may be a thermally expandable microcapsule foaming agent having a core-shell structure. More specifically, the encapsulated foaming agent has a core-shell structure including a core containing a hydrocarbon and a shell made of a thermoplastic resin formed on the core. Specifically, the hydrocarbon constituting the core is a liquid hydrocarbon having a low boiling point and is easily vaporized by heat. Therefore, when heat is applied to the encapsulated foaming agent, the thermoplastic resin constituting the shell softens and at the same time, the liquid hydrocarbon in the core is vaporized, and expands as the pressure inside the capsule increases, thereby forming bubbles larger than the existing size.

[0055] The hydrocarbon constituting the core of the encapsulated blowing agent may be one or more selected from the group consisting of n-propane, n-butane, iso-butane, cyclobutane, n-pentane, iso-pentane, cyclopentane, n-hexane, iso-hexane, cyclohexane, n-heptane, iso-heptane, cycloheptane, n-octane, iso-octane and cyclooctane. Among them, hydrocarbons having 3 to 5 carbon atoms (n-propane, n-butane, iso-butane, cyclobutane, n-pentane, iso-pentane, cyclopentane) are suitable for forming pores of the above-mentioned size, and iso-butane is the most suitable.

[0056] The thermoplastic resin constituting the shell of the encapsulated foaming agent may be a polymer formed from one or more monomers selected from the group consisting of (meth)acrylate compounds, (meth)acrylonitrile compounds, aromatic vinyl compounds, vinyl acetate compounds, and vinyl halide compounds. Among them, a copolymer of (meth)acrylate and (meth)acrylonitrile is most suitable for forming pores of the above-mentioned size.

[0057] In addition, such an encapsulated foaming agent may have a structure including a core containing a hydrocarbon and a shell surrounding the core and formed of a thermoplastic resin, have an average diameter before expansion of 5 to 30 μm, and have a maximum expansion ratio in air of 5 to 15 times.

[0058] The encapsulated blowing agent can be used in an amount of 0.005 to 1 part by weight based on 100 parts by weight of the acrylic acid monomer. If the content of the blowing agent is less than 0.005 part by weight, the blowing agent has little function as a blowing agent, and if the content of the blowing agent is more than 1 part by weight, the crosslinked polymer has too many pores, the gel strength of the produced superabsorbent resin is reduced, and the density is small, which may cause problems in distribution and storage.

[0059] In addition, in step 2, a surfactant that is generally used as a foam stabilizer may be added together with the carbonate foaming agent. Examples of such surfactants include alkyl sulfate compounds and polyoxyethylene alkyl ether compounds. Examples of the alkyl sulfate compounds include sodium dodecyl sulfate, ammonium lauryl sulfate, sodium lauryl ether sulfate, and sodium myreth sulfate, and examples of the polyoxyethylene alkyl ether compounds include polyoxyethylene lauryl ether. In this case, the alkyl sulfate compounds are anionic surfactants, and the polyoxyethylene alkyl ether compounds are nonionic surfactants.

[0060] The water content of the hydrogel polymer obtained by such a method may be about 40 to about 80% by weight. Meanwhile, in the present specification, the "water content" refers to the water content relative to the total weight of the polymer, and means the weight of the polymer minus the weight of the polymer in a dry state. Specifically, it is defined as a value calculated by measuring the weight loss due to evaporation of water in the polymer during the process of drying by increasing the temperature of the polymer by infrared heating. At this time, the drying conditions are a method of increasing the temperature from room temperature to about 180°C and then maintaining it at 180°C, and the total drying time is set to 20 minutes, including 5 minutes for the temperature increase step, and the water content is measured.

[0061] (Stage 3) Next, the hydrogel polymer is mixed with a reducing agent and then chopped. In this step, the reducing agent undergoes an oxidation-reduction reaction with the thermal polymerization initiator to reduce the thermal polymerization initiator, and the reduced thermal polymerization initiator induces an additional radical initiation reaction following the first radical initiation reaction in step 2. As a result, while the polymer is chopped, the residual monomers that could not participate in the polymerization reaction in step 2 are polymerized.

[0062] In this case, the reducing agent used is at least one sulfur-containing compound selected from the group consisting of sulfoxylates, sulfites, hydrogen sulfites, and metabisulfites, which can effectively undergo an oxidation-reduction reaction with the thermal polymerization initiator.

[0063] More specifically, the sulfoxylates are a mixture of a metal cation and a sulfoxylate ion (SO - ), and examples of the sulfoxylate include sodium formaldehyde sulfoxylate (Rongalite; HOCH2SO2Na), cobalt(II) sulfoxylate (CoSO2), and zinc sulfoxylate (ZnSO2).

[0064] In addition, the sulfites are a mixture of metal cations and sulfite ions (SO3 -), and examples of the sulfite include sodium sulfite (Na2SO3), potassium sulfite (K2SO3), and calcium sulfite (CaSO3).

[0065] In addition, bisulfites are a mixture of metal cations and bisulfite ions (HSO3 - ), and examples of the hydrogen sulfite include sodium hydrogen sulfite (NaHSO3), potassium hydrogen sulfite (KHSO3), and calcium hydrogen sulfite (Ca(HSO3)2).

[0066] Metabisulfites are also formed by combining metal cations with the metabisulfite ion (S2O5 - ), and examples of the metabisulfite include sodium metabisulfite (Na2S2O5), potassium metabisulfite (K2S2O5), and calcium metabisulfite (CaS2O5).

[0067] For example, the reducing agent may be sodium formaldehyde sulfoxylate (HOCH2SO2Na), sodium sulfite (Na2SO3), or sodium metabisulfite (Na2S2O5), which may be more advantageous in terms of efficiency in reducing the content of residual monomers.

[0068] In addition, the reducing agent is used in an amount of 10 parts by weight or more relative to 100 parts by weight of the thermal polymerization initiator. If the reducing agent is used in an amount of less than 10 parts by weight relative to 100 parts by weight of the thermal polymerization initiator, the reducing agent cannot effectively undergo an oxidation-reduction reaction with the thermal polymerization initiator, and it becomes difficult to simultaneously reduce the content of the residual monomer and the content of the water-soluble component in the superabsorbent resin.

[0069] More specifically, the reducing agent can be used in an amount of 10 parts by weight to 100 parts by weight per 100 parts by weight of the thermal polymerization initiator. If the reducing agent is used in an excessive amount, a large amount of the reducing agent may remain unreacted, which may cause odor after drying and surface treatment at a high temperature. For example, the reducing agent can be used in an amount of 10 parts by weight or more, 15 parts by weight or more, or 20 parts by weight or more, and 80 parts by weight or less, 70 parts by weight or less, 60 parts by weight or less, or 50 parts by weight or less per 100 parts by weight of the thermal polymerization initiator.

[0070] In addition, the reducing agent can be used in an amount of 0.1 to 1 mole per mole of the thermal polymerization initiator, taking into consideration the content of the thermal polymerization initiator remaining after the polymerization step and the cost aspect. More specifically, the reducing agent can be used in an amount of 0.15 moles or more, 0.2 moles or more, 0.25 moles or more, or 0.3 moles or more, and 0.8 moles or less, 0.7 moles or less, 0.65 moles or less, or 0.6 moles or less per mole of the thermal polymerization initiator.

[0071] Further, the reducing agent can be used in an amount of 0.01 to 0.1 parts by weight based on 100 parts by weight of the acrylic acid monomer. More specifically, the reducing agent can be used in an amount of 0.015 parts by weight or more, 0.02 parts by weight or more, 0.025 parts by weight or more, or 0.03 parts by weight or more, and 0.09 parts by weight or less, 0.08 parts by weight or less, 0.07 parts by weight or less, or 0.06 parts by weight or less based on 100 parts by weight of the acrylic acid monomer.

[0072] The method of mixing such a reducing agent with the hydrogel polymer is not particularly limited as long as it can be uniformly mixed with the hydrogel polymer, and can be appropriately adopted and used. Specifically, the reducing agent can be mixed in a dry state, dissolved in a solvent and then mixed in a solution state, or melted and then mixed.

[0073] Among these, for example, the reducing agent is mixed in a state of solution dissolved in a solvent. In this case, water is the most suitable solvent, considering that the reducing agent is a salt compound in which a metal cation and a sulfur-containing anion are combined, the ease of the drying process, and the cost of the solvent recovery system. In addition, the mixing of the solutions is performed by mixing the reducing agent and the hydrogel polymer in a reaction vessel, by putting the hydrogel polymer in a mixer and injecting the solution, or by continuously supplying the hydrogel polymer and the solution to a continuously operated mixer and mixing them.

[0074] After mixing the hydrogel polymer with a reducing agent, the mixture can be chopped to produce chopped hydrogel polymer.

[0075] Specifically, the shredding may include any one selected from the group of crushing equipment consisting of a vertical pulverizer, a turbo cutter, a turbo grinder, a rotary cutter mill, a cutter mill, a disc mill, a shred crusher, a crusher, a chopper, and a disc cutter, but is not limited to the above examples.

[0076] More specifically, the hydrogel polymer is chopped by a chopper, for example, a meat chopper. At this time, the chopping step is performed so that the particle size of the polymer is about 1 mm to about 10 mm. It is technically difficult to crush the polymer to a particle size of less than 1 mm due to the high water content of the hydrogel polymer, and the crushed particles may aggregate with each other. On the other hand, when the polymer is crushed to a particle size of more than 10 mm, the efficiency of the subsequent drying step is not increased significantly.

[0077] For this purpose, the meat chopper includes a chopping module including one or more perforated plates, and the perforated plate (when there are two or more perforated plates, each of the two or more perforated plates) may have a number of chopping holes having a certain size through which the hydrogel polymer can pass. The hole size of the chopping holes of the perforated plate may be 1 mm to 16 mm. In other words, the chopping is performed by extruding the hydrogel polymer so that it can be crushed while passing through the chopping holes of the perforated plate. In this case, an extruder is used to extrude the hydrogel polymer, and for example, a single or multiple screw type extruder is used.

[0078] (Stage 4) Next, the hydrogel polymer chopped in step 3 is dried and pulverized to form a powdered base resin.

[0079] The drying temperature in the drying step may be about 150 to about 250° C. If the drying temperature is less than 150° C., the drying time becomes too long, and the physical properties of the finally formed superabsorbent resin may be deteriorated, and if the drying temperature exceeds 250° C., only the polymer surface may be dried excessively, and fine powder may be generated in the subsequent pulverization process, and the physical properties of the finally formed superabsorbent resin may be deteriorated. Therefore, the drying is preferably performed at a temperature of about 150 to about 200° C., more preferably at a temperature of about 170 to about 200° C.

[0080] Meanwhile, the drying time is about 20 to about 90 minutes in consideration of process efficiency, but is not limited thereto.

[0081] The drying method in the drying step can be selected and used without any limitation on the configuration as long as it is one that is usually used in the drying process of a hydrogel polymer. Specifically, the drying step can be carried out by a method such as hot air supply, infrared radiation, ultrashort wave radiation, or ultraviolet radiation. The water content of the polymer after such a drying step may be about 5 to about 10% by weight.

[0082] Next, the dried polymer obtained through the drying step is pulverized. At this time, the pulverization is performed to obtain a powder containing particles having a particle size of about 150 to about 850 μm. Specific examples of the pulverizer used to pulverize to such a particle size include a pin mill, a hammer mill, a screw mill, a roll mill, a disc mill, and a jog mill, but the present invention is not limited to the above examples.

[0083] After the pulverization step, the base resin obtained after pulverization is classified according to particle size in order to control the physical properties of the superabsorbent resin powder that is finally manufactured. Preferably, polymers having a particle size of about 150 to about 850 μm are classified, and only the base resin having such a particle size can undergo the surface crosslinking reaction step. At this time, the particle size is measured according to the EDANA WSP220.3 method of the European Disposables and Nonwovens Association (EDANA).

[0084] The base resin may have an Ideal Hydrogel Index (IHI) of more than 19, as calculated by the following formula 1:

[0085] [Number 1] Ideal Hydrogel Index(IHI)=(CRC+8.7) / [ln{E / C+(RM / 500)}]

[0086] In the above formula 1, CRC is the centrifugal retention capacity measured by the EDANA method NWSP241.0.R2; E / C is the content of water-soluble components measured by the EDANA method WSP270.2, RM means the content of residual monomer remaining in the superabsorbent polymer as measured by the EDANA method NWSP210.0.R2.

[0087] Specifically, the base resin may have an Ideal Hydrogel Index (IHI), calculated by the above formula 1, of 19.3 or more, 19.5 or more, or 19.7 or more, and may be 23 or less, 22.5 or less, 22 or less, or 21.5 or less.

[0088] (Stage 5) Next, a step of forming a surface cross-linked layer on at least a part of the surface of the base resin by additionally cross-linking the surface of the base resin in the presence of a surface cross-linking agent is carried out, thereby producing a superabsorbent resin having a surface cross-linked layer formed on at least a part of the surface of the base resin, more specifically, on at least a part of the surface of each of the base resin particles.

[0089] The surface cross-linking is a step that increases the cross-linking density near the surface of the superabsorbent polymer particles relative to the cross-linking density inside the particles. Generally, the surface cross-linking agent is applied to the surface of the superabsorbent polymer particles. Thus, the reaction occurs on the surface of the superabsorbent polymer particles, which improves the cross-linking on the surface of the particles without substantially affecting the inside of the particles. Thus, the surface cross-linked superabsorbent polymer particles have a higher degree of cross-linking near the surface than inside.

[0090] The surface cross-linking agent can be any surface cross-linking agent that has been used in the manufacture of superabsorbent resins without any particular limitation. For example, the surface cross-linking agent can include one or more polyols selected from the group consisting of ethylene glycol, propylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, 1,2-hexanediol, 1,3-hexanediol, 2-methyl-1,3-propanediol, 2,5-hexanediol, 2-methyl-1,3-pentanediol, 2-methyl-2,4-pentanediol, tripropylene glycol and glycerol; one or more carbonate-based compounds selected from the group consisting of ethylene carbonate, propylene carbonate and glycerol carbonate; epoxy compounds such as ethylene glycol diglycidyl ether; oxazoline compounds such as oxazolidinone; polyamine compounds; mono-, di- or polyoxazolidinone compounds; cyclic urea compounds; polycarboxylic acid-based copolymers, etc.

[0091] According to one embodiment, the surface cross-linking agent may be the same as the internal cross-linking agent. For example, the surface cross-linking agent may include ethylene glycol diglycidyl ether. The ethylene glycol diglycidyl ether is highly water-soluble and has two epoxy groups, and the surface reaction can be easily carried out even at a relatively low temperature.

[0092] As an example, the surface cross-linking agent may include ethylene glycol diglycidyl ether and propylene glycol. Further, the surface cross-linking agent may include ethylene glycol diglycidyl ether, propylene glycol, and a polycarboxylic acid copolymer.

[0093] The content of the surface cross-linking agent can be appropriately selected depending on the type of the surface cross-linking agent to be added and the reaction conditions, and can be about 0.001 to about 5 parts by weight, preferably about 0.01 to about 3 parts by weight, and more preferably about 0.05 to about 2 parts by weight, relative to 100 parts by weight of the base resin. If the content of the surface cross-linking agent is too small, the surface cross-linking reaction hardly occurs, and if the content exceeds 5 parts by weight relative to 100 parts by weight of the base resin, the surface cross-linking reaction proceeds excessively, which may result in a decrease in water absorption properties such as water retention ability.

[0094] There is no limitation on the constitution of the method for mixing the surface crosslinking agent with the base resin. A method of putting the surface crosslinking agent and the base resin powder in a reaction tank and mixing them, a method of spraying the surface crosslinking agent onto the base resin powder, a method of continuously supplying the base resin and the surface crosslinking agent to a continuously operated mixer and mixing them, etc. can be used.

[0095] When the surface crosslinking agent is added, it may be added in the form of a surface crosslinking solution by mixing with water. When water is added, it has an advantage that the surface crosslinking agent can be uniformly dispersed in the polymer. At this time, the content of the added water is preferably about 1 to about 10 parts by weight per 100 parts by weight of the base resin in order to induce uniform dispersion of the surface crosslinking agent, prevent the polymer powder from clumping, and optimize the surface penetration depth of the surface crosslinking agent.

[0096] The temperature raising means for the surface crosslinking reaction is not particularly limited. Heating can be performed by supplying a heat medium or directly supplying a heat source. At this time, the type of heat medium that can be used can be a heated fluid such as steam, hot air, hot oil, etc., but the present invention is not limited to these, and the temperature of the heat medium to be supplied can be appropriately selected in consideration of the means of the heat medium, the heating rate, and the target temperature of the heat raising. On the other hand, examples of the heat source to be directly supplied include heating by electricity and heating by gas, but the present invention is not limited to the above examples.

[0097] After the surface cross-linked layer is formed on the surface of the base resin as described above, an inorganic substance can be further mixed therein.

[0098] The inorganic material may be, for example, one or more selected from the group consisting of silica, clay, alumina, a silica-alumina composite, and titania, and preferably, silica.

[0099] Such inorganic substances can be used in an amount of 0.01 parts by weight or more, or 0.05 parts by weight or more, or 0.1 parts by weight or more, and 5 parts by weight or less, or 3 parts by weight or less, or 1 part by weight or less, per 100 parts by weight of the superabsorbent resin.

[0100] Meanwhile, in order to control the physical properties of the superabsorbent polymer to be finally manufactured, a step of classifying the superabsorbent polymer obtained after the surface cross-linking reaction step according to particle size can be additionally carried out. Preferably, polymers having a particle size of about 150 to about 850 μm are classified, and only the superabsorbent polymer having such a particle size can be used as the final product.

[0101] The superabsorbent polymer obtained by such a manufacturing method may have a residual monomer content of 500 ppm or less as measured by EDANA method NWSP210.0.R2, and a water-soluble component content of less than 10 wt% as measured by EDANA method WSP270.2.Preferably, the superabsorbent polymer may have a residual monomer content of 400 ppm or less as measured by EDANA method NWSP210.0.R2, and a water-soluble component content of 7 wt% or less as measured by EDANA method WSP270.2.

[0102] The highly water-absorbent resin may have a centrifugation retention capacity (CRC) of 30 to 35 g / g, as measured by the EDANA method WSP241.3.

[0103] Furthermore, the highly water-absorbent resin may have an absorbency under pressure (AUP) of 18 to 25 g / g at 0.7 psi, as measured by the EDANA method WSP242.3.

[0104] The superabsorbent resin may have an Ideal Hydrogel Index (IHI) of 20 or more, as calculated by the following Equation 1:

[0105] [Formula 1] Ideal Hydrogel Index(IHI)=(CRC+8.7) / [ln{E / C+(RM / 500)}]

[0106] In the above formula 1, CRC is the centrifugal retention capacity measured by the EDANA method NWSP241.0.R2; E / C is the content of water-soluble components measured by the EDANA method WSP270.2, RM means the content of residual monomer remaining in the superabsorbent polymer as measured by the EDANA method NWSP210.0.R2.

[0107] More specifically, the superabsorbent resin produced by the above-mentioned production method may have a residual monomer content of 500 ppm or less, 450 ppm or less, 400 ppm or less, 390 ppm or less, or 380 ppm or less as measured by the EDANA method NWSP210.0.R2. Furthermore, the smaller the residual monomer content, the better, and the lower limit is theoretically 0 ppm, but for example, it may be 100 ppm or more, 150 ppm or more, or 200 ppm or more.

[0108] The superabsorbent polymer may have a water-soluble component content of less than 10% by weight, 9% by weight or less, 8% by weight or less, 7% by weight or less, 6.5% by weight or less, or 6.3% by weight or less, as measured by EDANA method WSP270.2. The lower the water-soluble component content, the better, and the theoretical lower limit is 0% by weight, but as an example, the water-soluble component content may be 3% by weight or more, 4% by weight or more, or 5% by weight or more.

[0109] In addition, the superabsorbent polymer may have a centrifuge retention capacity (CRC) measured by EDANA method WSP241.3 of 30 g / g or more, or 31 g / g or more and 35 g / g or less, or 33 g / g or less.

[0110] The superabsorbent polymer may also have an absorbency under pressure (AUP) at 0.7 psi, measured by the EDANA method WSP242.3, of 18 g / g or more, 20 g / g or more, or 21 g / g or more and 25 g / g or less, or 24 g / g or less.

[0111] Furthermore, the superabsorbent resin may have an Ideal Hydrogel Index (IHI) calculated by the above formula 1 of 20 or more, 20.5 or more, or 21 or more. The upper limit of the IHI value may be, for example, 25 or less, 24 or less, or 23 or less.

[0112] The present invention will be described in more detail with reference to the following examples, however, the following examples are merely illustrative of the present invention and are not intended to limit the scope of the present invention.

[0113] <Example> Preparation of encapsulated foaming agent As an encapsulated foaming agent used in the examples, F-36D manufactured by Matsumoto Co., Ltd. was prepared, which has a core of iso-butane and a shell of a copolymer of acrylate and acrylonitrile. At this time, the foaming start temperature (Tstart) of F-36D is 70°C to 80°C, and the maximum foaming temperature (Tmax) is 110°C to 120°C.

[0114] The diameter of each encapsulated foaming agent was measured by an optical microscope as the average Feret diameter, and the average value of the diameters of the encapsulated foaming agents was calculated and defined as the average diameter of the encapsulated foaming agents.

[0115] In addition, in order to confirm the expansion characteristics of the encapsulated foaming agent, 0.2 g of the prepared encapsulated foaming agent was applied to a glass Petri dish and then left on a hot plate preheated to 150° C. for 10 minutes. The encapsulated foaming agent gradually expands due to heat, and this was observed under an optical microscope to measure the maximum expansion ratio and the maximum expansion magnitude of the encapsulated foaming agent in air.

[0116] After applying heat to the encapsulated blowing agent, the diameter of the top 10% by weight of the particles that expanded the most was measured and defined as the maximum expansion magnitude, and the ratio (DM / D0) of the average diameter (DM) of the top 10% by weight of the particles that expanded the most after applying heat to the average diameter (D0) measured before applying heat to the encapsulated blowing agent was calculated and defined as the maximum expansion ratio.

[0117] The average diameter of the prepared encapsulated foaming agent before expansion was 13 μm, the maximum expansion ratio in air was about 9 times, and the maximum expansion size was about 80 to 150 μm.

[0118] Example 1 (Step 1) In a 3L glass container equipped with a stirrer and a thermometer, 100g of acrylic acid, 0.001g of an internal crosslinking agent PEGDA400 (polyethylene glycol diacrylate, Mw=400), 0.17g of ethylene glycol diglycidyl ether (EJ1030s), 0.008g of a photopolymerization initiator diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide (I-819) and 0.12g of a thermal polymerization initiator sodium persulfate (SPS) were added and dissolved, and then 188g of a 22% sodium hydroxide solution was added to prepare a monomer composition (neutralization degree: 75 mol%; solid content: 41 wt%).

[0119] (Step 2) 0.02 g of 28% sodium dodecyl sulfate (SDS) aqueous solution and 0.18 g of encapsulated foaming agent F-36D were added to the monomer composition. The monomer composition was then fed at a rate of 500 to 2000 mL / min onto a conveyor belt, 10 cm wide and 2 m long, rotating at a speed of 50 cm / min. Simultaneously with the feeding of the monomer composition, a 10 mW / cm 2 The polymerization reaction was allowed to proceed for 60 seconds under irradiation with ultraviolet light having an intensity of 1000 nm, thereby obtaining a sheet-like hydrogel polymer having a water content of 55% by weight.

[0120] (Step 3) Next, 0.032 parts by weight of sodium metabisulfite (SMBS; Na2S2O5, manufactured by Phueng Industrial Co., Ltd.) was dissolved in 54 g of water based on 100 parts by weight of the acrylic acid monomer, and the prepared sodium metabisulfite aqueous solution was sprayed onto the hydrogel polymer cut into a size of about 5 cm x 5 cm. This was then put into a meat chopper and chopped into hydrogel particle powder (crumb) having a size of 1 mm to 10 mm.

[0121] After (Step 4), the crumb was dried in an oven capable of changing the airflow up and down. Hot air of 185°C or higher was blown from bottom to top for 15 minutes, then from top to bottom for another 15 minutes to dry evenly, so that the moisture content of the dried material was 2% or less after drying. After drying, the crumb was pulverized in a pulverizer and classified to prepare a base resin by selecting a size of 150 to 850 μm.

[0122] (Step 5) Based on 100 g of the base resin, 4 g of water, 1.0 g of propylene glycol, 0.08 g of ethylene glycol diglycidyl ether, and 0.05 g of polycarboxylic acid copolymer (copolymer of methoxypolyethylene glycol monomethacrylate and methacrylic acid, Mw=40,000) were mixed to prepare a surface crosslinking solution. The surface crosslinking solution was sprayed and mixed into 100 g of the obtained base resin, and the mixture was placed in a vessel consisting of a stirrer and a double jacket, and a surface crosslinking reaction was carried out at 140° C. for 35 minutes. The surface-treated powder was then classified using a standard mesh sieve according to the ASTM standard to obtain a superabsorbent resin powder having a particle size of 150 to 850 μm. Then, 0.1 g of fumed silica (AEROSIL® 200) was added and mixed with 100 parts by weight of the obtained resin powder.

[0123] Example 2 A superabsorbent resin was prepared in the same manner as in Example 1, except that in step 3 of Example 1, sodium metabisulfite (SMBS; Na2S2O5) was used in an amount of 0.040 parts by weight based on 100 parts by weight of the acrylic acid monomer.

[0124] Example 3 A superabsorbent resin was prepared in the same manner as in Example 1, except that in step 3 of Example 1, 0.048 parts by weight of sodium metabisulfite (SMBS; Na2S2O5) was used relative to 100 parts by weight of the acrylic acid monomer.

[0125] Example 4 A superabsorbent resin was prepared in the same manner as in Example 1, except that in step 3 of Example 1, 0.056 parts by weight of sodium metabisulfite (SMBS; Na2S2O5) was used relative to 100 parts by weight of the acrylic acid monomer.

[0126] Comparative Example 1 A superabsorbent resin was produced using the same method as in Example 1, except that 0.05 g of sodium persulfate (SPS) and 0.2 g of ethylene glycol diglycidyl ether (EJ1030s) were used in the monomer composition of Example 1, and sodium metabisulfite (SMBS; Na2S2O5) was not used in step 3 of Example 1.

[0127] Comparative Example 2 A superabsorbent resin was produced in the same manner as in Example 1, except that 0.024 g of sodium persulfate (SPS) and 0.2 g of ethylene glycol diglycidyl ether (EJ1030s) were used in the monomer composition of Example 1, and sodium metabisulfite (SMBS; Na2S2O5) was not used in step 3 of Example 1.

[0128] Comparative Example 3 A superabsorbent resin was produced using the same method as in Example 1, except that 0.04 g of sodium persulfate (SPS) and 0.2 g of ethylene glycol diglycidyl ether (EJ1030s) were used in the monomer composition of Example 1, and sodium metabisulfite (SMBS; Na2S2O5) was not used in step 3 of Example 1.

[0129] Example 5 (Step 1) In a 3L glass container equipped with a stirrer and a thermometer, 100g of acrylic acid, 0.5g of an internal crosslinking agent PEGDA400 (polyethylene glycol diacrylate, Mw=400), 0.005g of allyl methacrylate (AMA), 0.008g of a photopolymerization initiator diphenyl(2,4,6-trimethylbenzoyl)-phosphine oxide (I-819), and 0.12g of a thermal polymerization initiator sodium persulfate (SPS) were added and dissolved, and then 188g of a 22% sodium hydroxide solution was added to prepare a monomer composition (neutralization degree: 75 mol%; solid content: 41 wt%).

[0130] (Step 2) 0.02 g of 28% sodium dodecyl sulfate (SDS) aqueous solution and 0.12 g of sodium bicarbonate were added to the monomer composition. The monomer composition was then fed at a rate of 500 to 2000 mL / min onto a conveyor belt, 10 cm wide and 2 m long, rotating at a speed of 50 cm / min. Simultaneously with the feeding of the monomer composition, a 10 mW / cm 2 The polymerization reaction was allowed to proceed for 60 seconds under irradiation with ultraviolet light having an intensity of 1000 nm, thereby obtaining a sheet-like hydrogel polymer having a water content of 55% by weight.

[0131] (Step 3) Next, 0.040 parts by weight of sodium metabisulfite (SMBS; Na2S2O5, manufactured by Phueng Industrial Co., Ltd.) was dissolved in 54 g of water based on 100 parts by weight of the acrylic acid monomer, and the resulting sodium metabisulfite aqueous solution was sprayed onto the hydrogel polymer cut into pieces of about 5 cm x 5 cm in size. This was then put into a meat chopper and chopped into hydrogel particle crumbs with sizes of 1 mm to 10 mm.

[0132] After (Step 4), the crumb was dried in an oven capable of changing the airflow up and down. Hot air of 185°C or higher was blown from bottom to top for 15 minutes, then from top to bottom for another 15 minutes to dry evenly, so that the moisture content of the dried material was 2% or less after drying. After drying, the crumb was pulverized in a pulverizer and classified to prepare a base resin by selecting a size of 150 to 850 μm.

[0133] (Step 5) Based on 100 g of the base resin, 4 g of water, 1.0 g of propylene glycol, 0.08 g of ethylene glycol diglycidyl ether, and 0.05 g of polycarboxylic acid copolymer (copolymer of methoxypolyethylene glycol monomethacrylate and methacrylic acid, Mw=40,000) were mixed to prepare a surface crosslinking solution. The surface crosslinking solution was sprayed and mixed into 100 g of the obtained base resin powder, and the mixture was placed in a container consisting of a stirrer and a double jacket, and a surface crosslinking reaction was carried out at 140° C. for 35 minutes. Thereafter, the surface-treated powder was classified using a standard mesh sieve according to the ASTM standard to obtain a superabsorbent resin powder having a particle size of 150 to 850 μm. Thereafter, 0.1 g of fumed silica (AEROSIL® 200) was added and mixed per 100 parts by weight of the obtained resin powder.

[0134] Comparative Example 4 A superabsorbent resin was produced in the same manner as in Example 5, except that in the monomer composition of Example 5, 0.24 g of sodium persulfate (SPS), 0.55 g of PEGDA400, and 0.0055 g of allyl methacrylate (AMA) were used, and sodium metabisulfite (SMBS; Na2S2O5) was not used in step 3 of Example 5.

[0135] Comparative Example 5 A superabsorbent resin was prepared in the same manner as in Example 1, except that in step 3 of Example 1, 0.006 parts by weight of sodium metabisulfite (SMBS; Na2S2O5) was used relative to 100 parts by weight of the acrylic acid monomer.

[0136] Experimental example: Measurement of the physical properties of superabsorbent resin The physical properties of the base resin and the superabsorbent resin prepared in the above examples and comparative examples were evaluated by the following methods, and are shown in Tables 1 and 2 below, respectively. Unless otherwise stated, all the processes for the evaluation of the physical properties below were carried out in a constant temperature and humidity room (23±0.5°C, relative humidity 45±0.5%), and the average value of three measurements was used as the measurement data to prevent measurement errors. In addition, the physiological saline or salt water used in the evaluation of the physical properties below refers to a 0.9 wt% sodium chloride (NaCl) aqueous solution.

[0137] (1)Centrifuge Retention Capacity (CRC) The water retention capacity of each resin was measured using EDANA WSP241.3, based on the water absorption capacity under no load.

[0138] Specifically, the highly water-absorbent resin W0(g) (approximately 0.2g) was evenly placed in a nonwoven envelope, sealed, and then immersed in physiological saline (0.9% by weight) at room temperature. After 30 minutes, the envelope was centrifuged at 250G for 3 minutes to remove water, and the mass W2(g) of the envelope was measured. The same procedure was also performed without the resin, and the mass W1(g) at that time was measured. Using the obtained masses, the CRC(g / g) was calculated using the following formula 2.

[0139] [Formula 2] CRC(g / g)={[W2(g)-W1(g)] / W0(g)}-1

[0140] (2) Absorbtion Under Pressure (AUP) The water absorption capacity of each resin at 0.7 psi was measured by EDANA method WSP242.3.

[0141] Specifically, a stainless steel wire mesh of 400 mesh was attached to the bottom of a plastic cylinder with an inner diameter of 60 mm. Under conditions of room temperature and humidity of 50%, superabsorbent resin W0(g) (0.90 g) was evenly spread on the wire mesh, and a piston capable of applying a load of 0.7 psi evenly on the wire mesh was made to be slightly smaller than the outer diameter of 60 mm, with no gap between it and the inner wall of the cylinder, and to ensure that the piston's up and down movement was not hindered. At this time, the weight W3(g) of the device was measured.

[0142] A glass filter with a diameter of 90 mm and a thickness of 5 mm was placed inside a Petri dish with a diameter of 150 mm, and physiological saline composed of 0.9% by weight of sodium chloride was placed at the same level as the upper surface of the glass filter. A sheet of filter paper with a diameter of 90 mm was placed on top of the glass filter. The measuring device was placed on the filter paper and the liquid was absorbed under a load for one hour. After one hour, the measuring device was lifted and its weight W4 (g) was measured.

[0143] Using the obtained masses, the water absorption capacity under pressure (g / g) was calculated according to the following formula 3.

[0144] [Formula 3] AUP(g / g)=[W4(g)-W3(g)] / W0(g)

[0145] (3) Water absorption rate (Vortex time) The water absorption rate (vortex time) of the superabsorbent resins of the above examples and comparative examples was measured by the following method.

[0146] (i) First, 50 mL of 0.9% salt water was poured into a 100 mL beaker with a flat bottom using a 100 mL mass cylinder.

[0147] (ii) Next, the beaker was placed in the center of a magnetic stirrer, and then a magnetic bar (diameter 8 mm, length 30 mm) was placed in the beaker.

[0148] (iii) Thereafter, the stirrer was operated so that the magnetic bar was stirring at 600 rpm, and the lowest point of the vortex generated by stirring was brought into contact with the magnetic bar.

[0149] (iv) After confirming that the temperature of the salt water in the beaker had reached 24.0°C, 2±0.01 g of the superabsorbent resin sample was added while simultaneously starting a stopwatch. The time until the vortex disappeared and the liquid surface became completely horizontal was measured in seconds, and this was regarded as the water absorption rate.

[0150] (4) 1 minute tap water absorption capacity The one-minute tap water absorbency of the superabsorbent resins of the Examples and Comparative Examples was measured by the following method.

[0151] (i) First, 1 g of a superabsorbent resin was placed in a tea bag measuring 15 cm in width and 30 cm in length, and the tea bag was immersed in 2 L of tap water and then allowed to swell for 1 minute.

[0152] (ii) Thereafter, the tea bag containing the swollen superabsorbent resin was lifted out of the tap water and after one minute had passed, the weights of the tea bag from which the tap water had been drained and the superabsorbent resin were both measured, and the weight of the empty tea bag was subtracted from the weight to obtain the one-minute tap water absorption capacity.

[0153] In this case, the tap water used had an electrical conductivity of 170 to 180 μS / cm when measured using Orion Star A222 (company: Thermo Scientific).

[0154] (5) Water soluble contents (Extractable contents, 16hr E / C) The water-soluble component content of the superabsorbent resins of the Examples and Comparative Examples was measured according to the method described in the EDANA method WSP270.2 standard of the European Disposables and Nonwovens Association.

[0155] Specifically, 1.0 g of the superabsorbent resin was placed in 200 g of 0.9 wt % NaCl solution, and after soaking for 16 hours while stirring at 500 rpm, the aqueous solution was filtered through filter paper. The filtered solution was first titrated with 0.1 N caustic soda solution at pH 10.0, and then back titrated with 0.1 N hydrogen chloride solution at pH 2.7, and the amount of non-crosslinked polymeric material was calculated and measured as water-soluble components from the amount required for neutralization.

[0156] (6) Residual monomer (RM) The residual monomer content of the superabsorbent resins of the Examples and Comparative Examples was measured according to the method described in the European Disposables and Nonwovens Association standard EDANA method NWSP210.0.R2(15) "Polyacrylate Superabsorbent Powders-Determination of the Amount of Residual Acrylate Monomers".

[0157] (7) Ideal Hydrogel Index (IHI) The IHI value was calculated by the above formula 1 based on the previously determined CRC, E / C and RM values ​​of each superabsorbent polymer.

[0158] (8) Permeability The liquid permeability of the superabsorbent resins of the above Examples and Comparative Examples was measured by the following method.

[0159] Specifically, with a piston placed in a chromatography tube (F20mm), lines were drawn on the liquid levels of 20mL and 40mL. The chromatography tube used had a length of 250mm and a diameter of 22mm, and was equipped with a 20mm diameter glass filter (Glass Fritted Filter Disc, P3: 16-40μm) and a lower valve (cock), and the piston had a weight of 65g so that a pressure of 0.3psi could be applied per unit area.

[0160] After this, the piston was removed, and water was poured in reverse to fill the tube to about 10 mL so as not to create air bubbles between the lower glass filter and the lower valve of the chromatography tube, and the tube was washed 2 to 3 times with 0.9 wt% salt water, and the salt water was filled to 40 mL or more. Next, the piston was inserted into the chromatography tube, the lower valve was opened, and the time (B) for the liquid level to decrease from 40 mL to the 20 mL mark was recorded.

[0161] Next, 10 mL of salt water was left in the chromatography tube, 0.2±0.0005 g of the classified (30#-50#) superabsorbent polymer sample was added, salt water was added to make the volume of the salt water 50 mL, and then the tube was left for 30 minutes. After that, a piston was placed in the chromatography tube and the tube was left for 1 minute, and the lower valve of the chromatography tube was opened, and the time (T1) for the liquid level to decrease from 40 mL to the 20 mL mark was recorded, and the time (unit: seconds) for T1-B was calculated using the following formula 4.

[0162] [Formula 4] Liquid permeability (sec)=T1-B

[0163] In the above formula 4, T1 is the time it takes for the liquid level to decrease from 40mL to 20mL after placing 0.2±0.0005g of classified (30#~50#) superabsorbent polymer sample in a chromatography tube, adding salt water to make the volume of salt water 50mL, and leaving it for 30 minutes. B is the time it takes for the liquid level in a chromatography tube filled with salt water to decrease from 40 mL to 20 mL.

[0164] [Table 1]

[0165] [Table 2]

[0166] As shown in Tables 1 and 2, the superabsorbent resins of Examples 1 to 4, in which a reducing agent capable of undergoing an oxidation / reduction reaction with a thermal polymerization initiator was added in a certain amount relative to the amount of the thermal polymerization initiator before drying of the hydrogel polymer, exhibit the same level of water absorption speed and liquid permeability as the superabsorbent resin of Comparative Example 2, which exhibits the same level of water absorption performance without using such a reducing agent, and the superabsorbent resin of Comparative Example 5, in which the reducing agent was used in an excessively small amount relative to the amount of the thermal polymerization initiator, while simultaneously reducing the amount of residual monomer and water-soluble components contained therein. It is also confirmed that all of the superabsorbent resins produced in the examples have an Ideal Hydrogel Index (IHI) of 20 or more.

[0167] In particular, when examining the physical properties of the base resins prepared in Comparative Examples 1 to 3, it can be seen that when the content of the thermal polymerization initiator increases, the content of the residual monomer decreases while the content of the water-soluble component increases significantly, and when the content of the thermal polymerization initiator decreases, the content of the water-soluble component decreases while the content of the residual monomer increases significantly. However, in the case of the base resins prepared in Examples 1 to 4 using a reducing agent, it can be confirmed that the content of the residual monomer and the content of the water-soluble component in the prepared superabsorbent resin can all be reduced by increasing the content of the reducing agent without adjusting the content of the thermal polymerization initiator.

[0168] In addition, the base resin of Example 5 was prepared by changing the type and content of the internal crosslinking agent from those of the superabsorbent resins of Examples 1 to 4. However, it can be seen that Example 5 also has a reduced residual monomer content and water-soluble component content compared to the base resin of Comparative Example 4 prepared without using a reducing agent in Example 5.

[0169] This shows that, regardless of the type of internal crosslinking agent used, when a reducing agent capable of undergoing an oxidation-reduction reaction with a thermal polymerization initiator is used in the shredding process before drying of the hydrogel polymer, it is possible to produce a superabsorbent resin in which the residual monomer content and water-soluble component content are reduced at the same time without decreasing various physical properties such as water absorption capacity, water absorption speed, and liquid permeability.

Claims

1. A step of preparing a monomer composition including an acrylic acid monomer having an acidic group, at least a part of which has been neutralized, an internal crosslinking agent, and a thermal polymerization initiator (step 1); Step 2: cross-linking the monomer composition to form a hydrogel polymer; mixing the hydrogel polymer with a reducing agent and then chopping the hydrogel polymer (step 3); Step 4: drying and pulverizing the hydrogel polymer chopped in step 3 to produce a base resin; and and (5) further cross-linking the surface of the base resin in the presence of a surface cross-linking agent to form a surface cross-linked layer on at least a portion of the surface of the base resin. The thermal polymerization initiator includes at least one selected from the group consisting of persulfate compounds, azo compounds, hydrogen peroxide, and ascorbic acid, and is used in an amount of 0.05 to 0.25 parts by weight based on 100 parts by weight of the acrylic acid monomer. The reducing agent is at least one selected from the group consisting of sulfoxylates and metabisulfites, and is used in an amount of 10 parts by weight to 100 parts by weight based on 100 parts by weight of the thermal polymerization initiator. A method for producing a superabsorbent resin.

2. The reducing agent is sodium formaldehyde sulfoxylate (HOCH 2 SO 2 Na), or sodium metabisulfite (Na 2 S 2 O 5 ) A method for producing the highly water-absorbent resin according to claim 1.

3. The reducing agent is mixed in a solution state dissolved in a solvent. A method for producing the highly water-absorbent resin according to claim 1 or 2.

4. The thermal polymerization initiator includes a persulfate compound. A method for producing the highly water-absorbent resin according to any one of claims 1 to 3.

5. The monomer composition further comprises a photopolymerization initiator. A method for producing the highly water-absorbent resin according to any one of claims 1 to 4.

6. A foaming agent is additionally used during the crosslinking polymerization of the monomer composition. A method for producing the highly water-absorbent resin according to any one of claims 1 to 5.

7. The superabsorbent resin has a residual monomer content of 500 ppm or less as measured by EDANA method NWSP210.0.R2, and a water-soluble component content of less than 10% by weight as measured by EDANA method WSP270.

2. A method for producing the highly water-absorbent resin according to any one of claims 1 to 6.

8. The superabsorbent resin has an Ideal Hydrogel Index (IHI) of 20 or more, as calculated by the following formula 1: A method for producing the superabsorbent polymer according to any one of claims 1 to 7: [Formula 1] Ideal Hydrogel Index (IHI) = (CRC+8.7) / [ln{E / C+(RM / 500)}] In the above formula 1, CRC is the centrifugation water retention capacity measured by the EDANA method NWSP241.0.R2; E / C is the content of water-soluble components measured by EDANA method WSP270.2, RM means the content of residual monomer remaining in the superabsorbent polymer as measured by the EDANA method NWSP210.0.R2.

Citation Information

Patent Citations

  • Production of water-swellable polymer

    JP1989062317A

  • Water absorbing resin composition and production thereof

    JP1992120111A

  • Treatment of water-absorbing resin

    JP1995062119A

  • Water absorbent resin and method for production thereof

    JP2006299234A

  • Production method for polyacrylic acid (SALT) water-absorbing resin

    JP2007291351A